Comparison Between The Efficacy Of Different Laboratory Methods For Diagnosis Of Cryptosporidium - Kadir, Mohammed A.; Othman, Nazakat F.; Salman, Yahya G. (The Iraqi Journal of Veterinary Medicine, 2004)
This study was performed to detect the effective laboratory method for diagnosis of Cryptosporidium spp. in patients attending the laboratories of Al-Tameem General Hospital and Kirkuk Paediatric Hospital in Kirkuk city, for the period from the beginning of January to end of August 2000.. It was shown that the modified Ziehl-Neelsens stain (hot method) with methylene blue (counter stain) was most efficient in identification of Cryptosporidium oocysts (4.36%), followed by malachite green (counter stain) (1.94%) and modified Ziehl-Neelsen (cold method) with malachite green (counter stain), safranin methylene blue, lugol s iodine preparation (mounting) (0.97%) for each and the modified Ziehl-Neelsen stain (cold method) with methylene blue (counter stain) was the least efficient (0.84%). .